MIND YOUR VIBE: NAVIGATING MENTAL HEALTH & SOCIAL MEDIA IN THE DIGITAL AGE FOR MUHAMMADIYAH YOUTH MOVEMENT - Istiqomah (Antis-publisher, 2026)
Objective: This community service activity aims to raise awareness among teenagers in Sidoarjo about mental health and the impact of social media on their well-being. Method: The method used involves Focus Group Discussions (FGD) and workshops, providing participants with a space to discuss the effects of social media on mental health, ways to manage digital stress, and building self-confidence. Additionally, practical strategies such as mindfulness and communication skills were introduced to help teenagers cope with digital pressures. Evaluation was conducted through participant feedback and group discussions to measure improvements in understanding mental health and media literacy. Results: The results showed a significant improvement in participants' understanding of how to manage stress arising from social media and maintain a balance between the digital world and real life. Novelty: The novelty of this program lies in its ability to integrate discussions on mental health with practical tools for managing social media pressures, providing a safe space for teenagers to address the challenges they face in the digital age and learn to navigate their interactions in the online world in a healthier way.